Behavioral Correlates of Depression Among Adults with Visual Impairments. (September 2021) - Haegele, Justin A.; Zhu, Xihe; Healy, Sean
Introduction : This study sought to examine: (a) the associations between physical activity, sedentary time, and sleep duration, as discrete behaviors, with depression among adults with visual impairments; and (b) the impact of meeting none, one, two, or three of the guidelines for these behaviors on depression among adults with visual impairments.Materials : One hundred eighty-two ( Mage = 44.8) adults with visual impairments, recruited via email through two visual impairment organizations in the United States, completed the International Physical Activity Questionnaire–Short Form, a sleep duration question, the Major Depression Inventory, and a demographic questionnaire. Based on results from the questionnaires, dichotomous variables for meeting or not meeting physical activity, sleep, and sitting guidelines were created. Data were analyzed using three components: a descriptive analysis, Pearson product-moment correlation analyses, and hierarchical regression analyses.Results : Overall, 14.8% of participants were categorized as having some degree of depression. Meeting the sleep guideline was a significant negative predictor of depression scores in the hierarchical regression analyses. The number of guidelines met was a negative predictor for depression score controlling for other variables.Discussion : Adequate sleep, as well as meeting all three guidelines synergistically, was meaningful in influencing depression among this population. The current study's results should prompt the continued examination of health-behaviors among adults with visual impairment using a more holistic 24-hour activity cycle framework.Implications for practitioners : This study supports the utilization of multi-behavioral interventions to reduce the risk of depression by enhancing physical activity and sleep, while reducing sitting time, among this population.